On Multivalued Nonexpansive Mappings in ℝ-Trees - K. Samanmit; B. Panyanak (Journal of Applied Mathematics)
The relationships between nonexpansive, weakly nonexpansive, *-nonexpansive, proximally nonexpansive, proximally continuous, almost lower semicontinuous, and ɛ-semicontinuous mappings in ℝ-trees are studied. Convergence theorems for the Ishikawa iteration processes are also discussed.